Brain amyloid load and cognitive trajectories in older individuals at risk for dementia. (December 2021) - Hossain, Gazi Saadmaan; Hall, Anette; Ngandu, Tiia; Kemppainen, Nina; Rinne, Juha O.; Kivipelto, Miia; Solomon, Alina
Abstract: Background: Most studies have so far investigated the cognitive performances and amyloid status on brain PET scans in cognitively normal, cognitively impaired, or individuals with dementia. In this study associations between brain amyloid status and changes in cognitive performance over time in an at‐risk older general population without dementia or substantial cognitive impairment were evaluated. Method: Forty‐eight individuals from the Finnish Geriatric Intervention Study to Prevent Cognitive Impairment and Disability (FINGER) main study participated in the 11C‐Pittsburgh compound B (PiB)‐positron emission tomography (PET) exploratory sub‐study. Participants were categorized as amyloid+ or amyloid– after baseline PET scans were assessed visually by two experienced readers. A comprehensive cognitive Neuropsychological Test Battery (NTB) was used to assess cognitive performance at baseline, 12‐ and 24‐month follow‐up. The Prospective and Retrospective Memory Questionnaire was used to measure subjective cognitive complaints (SCCs) during the study. Changes in cognitive functions during the 2‐year study were compared across baseline amyloid groups using mixed effects regression models with maximum likelihood estimation. Result: The mean age for all participants (n=48) was 71.4 years, and 22 participants (45%) were female. At baseline, 20 participants (42%) had amyloid+ PET scans and amyloid positivity was associated with lower NTB executive function (estimate = ‐0.38, 95% CI= ‐0.70 – ‐0.05, p=0.03). Interaction terms between baseline amyloid+ status and time were significant for NTB total score (estimate=‐0.10, 95% CI= ‐0.20 – ‐0.01, p=0.04) and NTB memory score (estimate = ‐0.18, 95% CI= ‐0.34 – ‐0.03, p=0.02). No significant associations were observed between amyloid positivity and change in NTB executive function score or NTB processing speed score. Furthermore, amyloid status was not significantly related to SCCs. Conclusion: Results from this study suggest that positive amyloid status is likely to reduce cognitive abilities over time. Interestingly, in this very early at‐risk stage before the onset of substantial impairment or dementia, amyloid status was related to poorer trajectories in global cognition and memory over time, but not to subjective cognitive complaints. However, future studies with larger sample sizes and longer follow up period will be needed to further investigate the impact of amyloid accumulation.